Aleitamento Materno Exclusivo e Desmame Precoce - Katia Valéria Manhabusque (Residência Pediátrica)
INTRODUCTION: This study is justified by its academic, scientific and social relevance, whose purpose is to investigate the main outcomes evident in the scientific literature to understand the main reasons that lead mothers to early weaning and non-adherence to exclusive breastfeeding until six months of life. OBJECTIVE: To demonstrate, through the scientific literature, factors related to adherence to exclusive breastfeediing up to six months of life. METHODOLOGY: This is a systematic review study, carried out through a survey of data in the scientific bases: LILACS, SciELO and MEDLINE. RESULTS: Inadequate prenatal care, absence of a support network and family support, use of pacificiers, maternal age, introduction of infant formulas are important factors for weaning before 6 months of life. CONCLUSION: Among all the factors associated with early weaning, puerperal care provided in health services, whether hospitalized or outpatient, is very important. This study provides information that can support actions to promote, protect and support breastfeeding, with guidance and knowledge being a tool to be used by health professionals.